A model for grinding forces prediction in ultrasonic vibration assisted grinding of SiCp/Al composites. Issue 9 (December 2016) - Zhou, Ming; Zheng, Wei
Abstract Ultrasonic vibration assisted grinding is an advanced method for machining difficult-to-process materials such as SiCp/Al composites. This paper presents a mechanics model for predicting grinding forces in ultrasonic vibration assisted grinding of SiCp/Al composites. It consists of side grinding force model and end grinding force model. In side grinding force model, the major components are the normal force and tangential force in which the analytical expressions for the chip formation force based on Rayleigh's probability density function, the frictional force, and the particle fracture force based on Griffith theory are established, respectively. In contrast, the axial force developed based on the indentation theory is the major component in end grinding force model. The coefficients in the proposed grinding force model were obtained through two groups of orthogonal experiments. Based on the mechanics prediction model, the relationship between grinding forces and process variables were predicted. At last, two groups of single factor experiments were conducted to verify the proposed grinding force model and experimental results were found to agree well with predicted results.